EXPLORING THE INFLUENCE OF BROKEN HOMES ON CHILDREN'S MINDSETS: A QUALITATIVE STUDY - Maharani, Annisa; Daulay, Annisa Arrumaisyah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
A broken home represents a distressing family crisis characterized by chaos, disorganization and a loss of purpose, which significantly impacts the mindset of children. This research aims to investigate the mindset of children who come from broken homes. Qualitative methods, accompanied by descriptive analysis, were used as a research approach. The study sought to examine the mindset of children before, during, and after experiencing a broken home. Before the occurrence of a broken home, children generally hold a mindset that perceives their family as a source of happiness and warmth. They view their parents as a reliable refuge, providing them with shelter and emotional support in all aspects of their lives. However, when confronted with a broken home situation, the children's mindset undergoes a notable transformation. They may experience feelings of hopelessness, believing they are unworthy of happiness. Consequently, they may exhibit a reluctance to engage in social interactions, encounter unmet needs, neglect their educational and home responsibilities, and develop feelings of fear and pessimism. Following the experience of a broken home, children gradually rebuild their mindset. They work towards regaining their lost self-concept that was impacted by the divorce or separation. This process often involves fostering independence and striving to achieve personal goals. It is important to note that a child's mindset tends to evolve as they grow older and gain more knowledge and experiences, ultimately contributing to a more developed mindset.